Bilateral nanophthalmos, pigmentary retinal dystrophy, and angle closure glaucoma–a new syndrome?. Issue 8 (August 1985) - Ghose, S; Sachdev, M S; Kumar, H
Abstract : An unusual case of bilateral nanophthalmos with pigmentary retinal dystrophy and angle closure glaucoma is presented. This is probably the first published report of the established association of all these three entities in the same patient. The aetiological possibilities and clinical significance are discussed.